Inadequacy and impact of facility design for adolescents and young adults with cancer. (June 2020) - Peditto, Kati; Shepley, Mardelle; Sachs, Naomi; Mendle, Jane; Burrow, Anthony
Abstract: As cancer remains the leading disease-related cause of death in adolescence, designers must consider the influence of health facility design on social support and quality of life, while considering the changing psychosocial needs of adolescents and young adults (AYAs). Both the stress of treatment and the environment in which treatment occurs can influence AYAs during a time of significant social, biological, and cognitive developmental transitions. A questionnaire developed and provided to 104 AYA-aged survivors of AYA cancer revealed significant inadequacies across 22 features of the cancer treatment environment. Results of a regression analysis suggest a significant relationship between adequacy of the built environment, social support, AYA-specific resources, and health-related quality of life. Recommendations are provided for the design of an inpatient or outpatient cancer facility for young people, such that designers must create space to balance desired and achieved social interaction. Highlights: Cancer facilities for adolescents and young adults (AYAs) are significantly inadequate. The built environment, social support, and AYA resources can help predict quality of life. AYAs may benefit from environments providing choice, control, and privacy. Designers should consider a spectrum of public to private spaces.